Characterization of rat models of type two diabetes and metabolic syndrome and the evaluation of SDF-1 mRNA as a treatment for erectile dysfunction - Pallas, Wrenn D (East Carolina University, 2023)
Erectile Dysfunction (ED) affects a considerable population of men and can have a profound negative impact on their quality of life and well-being. ED is often a consequence of age and diseases that affect the microvasculature and nervous tissue, including hypertension, dyslipidemia, diabetes, and metabolic syndrome. Currently available ED treatments are moderately effective at best, and only address the symptoms, not the underlying causes. A treatment that is effective in diabetic patients suffering with ED is sorely needed. To address this need, we have been investigating a regenerative gene therapy based on stromal cell-derived factor-1 (SDF-1). SDF-1 is a highly conserved chemokine that regulates endogenous repair pathways by directing stem cell migration to the site of injury. In chapter two, we characterized the metabolic, vascular, and erectile function of the ZDF and ZSF-1 rat models of type two diabetes (T2DM) and metabolic syndrome (MetS), respectively. By 30 weeks of age, ZDF obese rats had severe T2DM, and ZSF-1 obese rats developed MetS present with obesity, mild hyperglycemia, and hypertension. Both ZDF and ZSF-1 obese rats had vascular complications such as aortic endothelial dysfunction and had ED as demonstrated by lower intracavernosal pressure to mean arterial pressure (ICP/MAP). In chapter three, we investigated the effects of SDF-1 mRNA (mSDF-1) on the erectile function of the ZDF rat model of T2DM. ZDF rats were aged to 30 weeks and mSDF-1 was administered via penile injections every 5 days for a total of 4 injections. mSDF-1 increased ICP/MAP and maximal ICP indicating that it does improve erectile function. mSDF-1 treatment did not affect heart, spleen, kidney, bladder, testes, or seminal vesicle weights or complete blood counts (CBC) indicating that it appears to be a safe treatment. Overall, we believe that mSDF-1 has the potential to treat diabetic patients suffering with ED.
Keywords: Sexual Medicine; Erectile Dysfunction; Male; Rats; Animals; Metabolic Syndrome; Diabetes Mellitus; Risk Factors